2014
DOI: 10.1039/c3pp50327e
|View full text |Cite
|
Sign up to set email alerts
|

New cyclometallated Ru(ii) complex for potential application in photochemotherapy?

Abstract: In an effort to create a molecule that absorbs further into the optimum window for photochemotherapy (PCT), the new cyclometallated complex [Ru(biq)2(phpy)](PF6) (1, biq = 2,2'-biquinoline, phpy(-) = deprotonated 2-phenylpyridine) was synthesized, characterized and compared to the known photoactive complexes [Ru(biq)2(bpy)](PF6)2 (2, bpy = 2,2'-bipyridine) and [Ru(biq)2(phen)](PF6)2 (3, phen = 1,10-phenanthroline), both of which undergo exchange of one biq ligand when irradiated with red light in coordinating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 56 publications
4
50
1
Order By: Relevance
“…5). A similar trend was reported for the photochemically inert complex [Ru(biq) 2 (phpy)] + (phpy À = deprotonated 2-phenylpyridine), which emits at 980 nm in CH 3 CN at 77 K (47). It should also be noted that the shorter excited state lifetime in 2 compared to 1 is consistent with the lower energy of the emissive state in the former relative to the latter, as predicted by the energy gap law (49,50).…”
Section: Photochemistrysupporting
confidence: 81%
See 1 more Smart Citation
“…5). A similar trend was reported for the photochemically inert complex [Ru(biq) 2 (phpy)] + (phpy À = deprotonated 2-phenylpyridine), which emits at 980 nm in CH 3 CN at 77 K (47). It should also be noted that the shorter excited state lifetime in 2 compared to 1 is consistent with the lower energy of the emissive state in the former relative to the latter, as predicted by the energy gap law (49,50).…”
Section: Photochemistrysupporting
confidence: 81%
“…The quantum yields for the dpb ligand exchange in 1 were measured to be Φ 550 = 0.015(4) and Φ 600 = 0.0094(8) in H 2 O; these values are slightly lower than those reported for 4 under similar conditions, Φ 550 = 0.020(3) and Φ 600 = 0.024(2) . The lower quantum yields for 1 can be attributed to the poor solubility of the dpb ligand relative to the biq ligand in H 2 O, which would make the escape from the solvent cage less favorable for the former and its subsequent recombination to regenerate 1 more likely.…”
Section: Resultsmentioning
confidence: 83%
“…Such bathochromic absorption is in agreement with the extremely low reduction potentials measured by cyclic voltammetry. It should be noted that ruthenium(II) complexes absorbing red light are rare, and have scarcely been reported in the literature …”
Section: Resultsmentioning
confidence: 99%
“…reported that 13p is not an optimal compound for PDT due to its high cytotoxicity in the dark and its lack of photochemical sensitivity. 230 They found a 7-fold increase in the cytotoxicity of cycloruthenated complex 13p upon irradiation with light at 639 nm.…”
Section: Ruthenium(ii) Polypyridyl Complexesmentioning
confidence: 98%